2009
DOI: 10.1021/bm900701m
|View full text |Cite
|
Sign up to set email alerts
|

Alkylamino Hydrazide Derivatives of Hyaluronic Acid: Synthesis, Characterization in Semidilute Aqueous Solutions, and Assembly into Thin Multilayer Films

Abstract: A series of biodegradable alkylamino hydrazide hyaluronic acid (HA) derivatives were prepared and used to design new biocompatible films able to release hydrophobic drugs in a controlled manner. The first step of this work thus consisted in optimizing the synthetic conditions of hydrazide HA derivatives bearing pendant hexyl, octyl, decyl, and citronellyl chains with a degree of substitution of 0.05 or 0.10. The behavior in aqueous solution of these water-soluble modified HA samples was then examined in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…HA bearing 20 alkyl chain of 10 carbons every 100 repeating disaccharide units (degree of substitution (DS) of 0.2), and quaternized derivative of chitosan (QCHI) were synthesized following a previously published protocol [37,44]. The substitution degree of CHI was of 1.1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…HA bearing 20 alkyl chain of 10 carbons every 100 repeating disaccharide units (degree of substitution (DS) of 0.2), and quaternized derivative of chitosan (QCHI) were synthesized following a previously published protocol [37,44]. The substitution degree of CHI was of 1.1.…”
Section: Methodsmentioning
confidence: 99%
“…In order to load PTX into the films, PTX was pre-complexed with hydrophobic HA20C10, which has a very high affinity for hydrophobic molecules [37]. Indeed, we have previously shown that the fluorescence intensity of aqueous solutions of alkylated HA derivatives containing the hydrophobic dye Nile Red (NR) strikingly depended on the length of the alkyl chain [37], the C10 derivatives exhibiting the highest capacity to form hydrophobic nanodomains.…”
Section: Ptx Entrapment In Pem Filmsmentioning
confidence: 99%
See 3 more Smart Citations